Natural gas transmission and distribution business - Paliwal, Pramod; Yadav, Sudhir (Boca Raton, FL : CRC Press, 2018)
The natural gas business consists of two major aspects, sourcing and transportation, and distribution has been a growing area of interest to industry, government and academia. With the emphasis on promoting natural gas sector, there is an increasing need to have a well documented book that deals with the business issues, particularly the transportation and distribution of this sector, specifically aimed at petroleum engineers and professionals. This book fills this gap to provide structured material that deals with managerial and regulatory aspects with an applied technical perspective wherever needed.
Natural gas industry-an introduction -- Regulatory aspects of natural gas transmission and distribution business -- Natural gas transmission business: project management aspects -- Natural gas transmission business: operations and maintenance aspects -- Natural gas distribution business: project management aspects -- Natural gas distribution business: operations and maintenance aspects -- Natural gas transmission and distribution business: health, safety & environment issues -- Marketing aspects of natural gas transmission and distribution business -- Innovation in natural gas distribution: the case of LNG Express.
OCLC-licensed vendor bibliographic record.
Keywords: Gas industry; Gas companies; Natural gas pipelines; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; BUSINESS & ECONOMICS / Management Science; TECHNOLOGY / Engineering / General; TECHNOLOGY / Engineering / Chemical & Biochemical